Distributed energy resource participation in electricity markets: A review of approaches, modeling, and enabling information and communication technologies. (September 2022) - Stekli, Joseph; Bai, Linquan; Cali, Umit; Halden, Ugur; Dynge, Marthe Fogstad
Abstract: The continued development of distributed energy resources (DER), information and communications technologies is enabling a greater number of parties to participate in electricity markets. This review explores the various methods that DERs may utilize to participate in electricity markets, the differing architectures and methodologies used to model their participation, the past and future development of communications technologies that has enabled this participation, and examples of commercial implementations of solutions to DER participation in electricity markets. Highlights: Approaches and modeling architecture for DER participation in electricity markets is explored. Modeling solution methodologies to DER electricity market approaches is reviewed. Communication technologies that have allowed for increased deployment of DER technologies is examined. Current commercial applications of the approaches for DER participation in electricity markets is identified.